2022
DOI: 10.1016/j.heliyon.2022.e08869
|View full text |Cite
|
Sign up to set email alerts
|

Association between demographic characteristics, lower limb range of motion, functional performance, ability to dual task, quality of life and risk of falls in older adults of the United Arab Emirates - A cross-sectional study

Abstract: Background: With increasing age, decreased range of motion of lower limb joints, impaired functional performance and balance, pain status, altered dual tasking, and poor quality of life may predict the risk for falls in older adults. Therefore, this study aimed to identify which of the aforementioned variables and demographic factors predict falls in older adults in the United Arab Emirates. In addition, the study examined the association between demographic characteristics and the risk of falls in older adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…The mean score of the Thai-HFHAT-SF was highest in the elderly group. This was due to most of the elderly having health issues with falling being one of the health issues posing a serious threat to their health [22,23], causing them to sensitively focus on home hazards that could potentially cause fall risk while taking the instrument. The mean score in the VHV group was the lowest, which was consistent with findings reported by Morgan and coworkers (2005).…”
Section: Discussionmentioning
confidence: 99%
“…The mean score of the Thai-HFHAT-SF was highest in the elderly group. This was due to most of the elderly having health issues with falling being one of the health issues posing a serious threat to their health [22,23], causing them to sensitively focus on home hazards that could potentially cause fall risk while taking the instrument. The mean score in the VHV group was the lowest, which was consistent with findings reported by Morgan and coworkers (2005).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoglycemic symptoms are highly correlated with falls. In the study of [27] lower extremities active ROM was found to be significantly associated with the risk of falls in older adults in univariate analysis. Jung et al [28] assessed that reduced hip flexion, hip external rotation and ankle dorsiflexion ROMs are important risk factors for falls in older women.…”
Section: Multivariate Analysismentioning
confidence: 98%